2022
DOI: 10.7759/cureus.30667
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes Following Cemented Versus Cementless Robotic-Assisted Total Knee Arthroplasty

Abstract: Background: Cemented fixation during total knee arthroplasty (TKA) has long been the gold standard due to excellent survivorship and clinical outcomes. With recent biomaterial advancements, cementless fixation has gained renewed interest. Most studies demonstrate similar clinical outcomes and survivorship between these two fixation methods, without consensus regarding the optimal method of fixation during TKA. Outcomes following TKA also depend upon the proper alignment and positioning of components. Robotic-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
2
4
1
2
Order By: Relevance
“…In our retrospective cohort, we found that the cemented group had a higher rate of return to the operating room than the cementless group (1.8% vs 3.3%). This differs from the single surgeon study by McCormick et al., which found no differences [ 23 ]. The most common indication for return to the operating room in both groups was MUA for stiffness.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In our retrospective cohort, we found that the cemented group had a higher rate of return to the operating room than the cementless group (1.8% vs 3.3%). This differs from the single surgeon study by McCormick et al., which found no differences [ 23 ]. The most common indication for return to the operating room in both groups was MUA for stiffness.…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, we found that the majority of the cases at our institution that were being done using robotic technology also were using press fit technology. Our study’s results are similar to the results of the only other study comparing cementless vs cemented Ra-TKA, which was a single surgeon series [ 23 ]. Our series included 19 surgeons between 2 hospitals within a single healthcare system and had a larger patient population.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations